Pengaruh Keadilan Distributif dan Keadilan Prosedural terhadap Turnover Intention dengan Kepuasan Kerja sebagai Variabel Mediasi - Ezha Fericko Yudhian; Sigit Wibowo D N; Devani Laksmi Indiyastuti (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2020)
This research is a survey on Koperasi Bangun Sejahtera which is located in purwokerto. The aims of this study is to find out the effect distributive Justice and procedural Justice on Koperasi Bangun Sejahtera’s turnover intention with job satisfaction as a mediation variable. There were 54 employees chosen as respondent of the research. Then saturation sampling method was used to determine the respondent. This research using SPSS Software with Multiple Regression analysis technique method. The result showed that procedural and distributive justice affect turnover intention, and the effect was mediated by job satisfaction.